EFEKTIVITAS PELAYANAN KESEHATAN DI PUSKESMAS - Lisna Novita; Dina Deviana Anggraeni (STISIP Widyapuri Mandiri Sukabumi, 2023)
The effectiveness of health services at the Nagrak Health Center in Nagrak Sub-district, Sukabumi District is not yet fully optimal. One of the reasons is the lack of effectiveness in the services provided by medical personnel. Therefore, the author is interested in examining the effectiveness of health services at the Nagrak Health Center using the effectiveness theory approach. According to Saxena in Indrawijaya (2014: 176), effectiveness is a measure of the extent to which targets (both in terms of quantity, quality, and time) can be achieved. The greater the target that can be achieved, the higher the level of effectiveness. This approach emphasizes the results produced by a service rather than problems that may arise in the use of resources. The research method used in this research is descriptive analysis qualitative research method. The focus of this research is on the Effectiveness of Health Services at the Nagrak Health Center, Nagrak District. There were six research informants selected using purposive sampling and snowball sampling methods. Research informants include the Head of the Puskesmas, Health Workers, Administrative Staff, and the Community. Data were collected through interviews, observation, and documentation. To ensure data validity, source triangulation, technique triangulation, and time triangulation were conducted. Data analysis was conducted through data processing, data presentation, data reduction, and conclusion drawing/verification. The results showed that the better the health service, the more effective the service. Thus, to improve the effectiveness of health services at the Nagrak Health Center, Nagrak Subdistrict, Sukabumi Regency, it is necessary to make improvements in service aspects to be more effective for the community. Thus, it is hoped that the effectiveness of health services can be achieved.